Effects of reduced seawater pH on nematode community composition and diversity in sandy sediments. (September 2019) - Hua, Er; Sun, Yantao; Zhang, Zhinan; He, Lei; Cui, Chunyan; Mu, Fanghong
Abstract: The present study investigated the potential effects of seawater acidification on the taxonomic structure and diversity of nematode communities using a microcosm experiment. Nematode samples for the microcosm experiment were collected from the low tidal zone of two sandy beaches with different sediment compositions (medium sand vs. very fine sand) in Qingdao (China). In the microcosm, nematode communities were exposed to nine experimental treatments comprising two pH levels for 56 days: 8.0 (ambient control) and 7.3. Communities were exposed for 0, 7, 14, 28, or 56 days. Results showed that the most distinguishable differences in nematode community structure and diversity indices were caused by sediment type. Reduced pH changed the taxonomic structure of nematode communities in medium sand sediments. An increase in species with higher tolerance to lowered pH occurred as a response and resulted in increased diversity in medium sand sediments. Nematode communities in finer sediments appeared less sensitive to reduced pH. Highlights: Reduced pH changed nematode community composition in medium sand sediment. Reduced pH increased nematode diversity in medium sand sediments. Proportion of nematodes with higher tolerance to lowered pH increased in medium sand. Nematode communities in finer sediments appeared less sensitive to reduced pH.